AN ANALYSIS OF PERCEIVED SOCIAL SUPPORT AND HOPELESSNESS LEVELS FROM FAMILIES WİTH SCHIZOPHRENIC PATIENTS IN TERMS OF VARIOUS VARIABLES - Ayşe Eliüşük BÜLBÜL; Hüseyin IZGAR (International Journal of Eurasia Social Sciences, 2017)
In this study, the significance levels between perceived social support and hopelessness of families with schizophrenia were examined. The independent variables of this study were; gender, age, marital status, educational status, social security and family type. Dependent variables are hopelessness and perceived social support. The general scope of the study consists of families with schizophrenic patients, which are living in Konya and districts of Konya. The sample of the research was selected by a random cluster sampling method from families with schizophrenic patients living in Konya. The sample of the study consists of 152 families with schizophrenic patients. To determine the level of Perceived Social Support of the patient's families, "Multidimensional Perceived Social Support Scale" was used and to determine de the level of hopelessness, the "Beck Hopelessness Scale" was used. The average of the perceived social support and hopelessness scores were compared by gender, marital status, social security, family type, educational status, age, marital status and the difference between the groups' averages, were assessed using the t test. The analysis of the relationship between Hopelessness and Perceived Social Support scores was made by help of the Pearson Moments Product Correlation Coefficient technique. Whether the perceived level of social support and hopelessness differes according to the age and educational status variables or not, were tested by variance analysis and Tukey Test was used as a further analysis. Findings obtained in the research; it was observed that the perceived hopelessness scores according to age variables in families with schizophrenic patients did not differ according to the total hopelessness, hopes, and future expectation scores; but in contrast, it became different in their motivational subscale. According to the results of the research; a negative relationship was found between the perceived social support scores of families with schizophrenic patients and the hopelessness scores of families with schizophrenic patients. As perceived social support increases, hopelessness scores decrease.